2013
DOI: 10.7780/kjrs.2013.29.2.2
|View full text |Cite
|
Sign up to set email alerts
|

Turbid water atmospheric correction for GOCI: Modification of MUMM algorithm

Abstract: :The early Sea-viewing Wide Field-of-view Sensor(SeaWiFS) atmospheric correction algorithm which is the basis of the atmospheric correction algorithm for Geostationary Ocean Color Imager(GOCI) assumes that water-leaving radiances is negligible at near-infrared(NIR) wavelengths. For this reason, all of the satellite measured radiances at the NIR wavelengths are assigned to aerosol radiances. However that assumption would cause underestimation of water-leaving radiances if it were applied to turbid Case-2 waters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…In the absence of in situ data, the results of the new algorithm (represented by QSV) are compared with those processed by the B2010 [33], A2012 [34], and L2013 [35] algorithms. VIIRS and GOCI Level-1 data were obtained online (https://oceancolor.gsfc.nasa.gov).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the absence of in situ data, the results of the new algorithm (represented by QSV) are compared with those processed by the B2010 [33], A2012 [34], and L2013 [35] algorithms. VIIRS and GOCI Level-1 data were obtained online (https://oceancolor.gsfc.nasa.gov).…”
Section: Resultsmentioning
confidence: 99%
“…Numerous red/NIR modeling approaches have been investigated to deal with non-zero ρ w (red/NIR) values within the AC process. Three kinds of AC approaches are briefly reviewed herein-the B2010 AC algorithm proposed by Bailey et al [33] is currently adopted in SeaDAS, while the A2012 algorithm proposed by Ahn et al [34] and the L2013 algorithm proposed by Lee et al [35] are implemented in GDPS.…”
Section: Previous Ac Algorithmsmentioning
confidence: 99%
“…Ryu et al (2002) and Shen et al (2008) showed that in tidal flat zones, thermal-infrared (TIR) band is the most sensitive to the location of waterline through density slicing. Work on Landsat has shown that mid-infrared bands (band 5 in the case of Landsat TM) is the most suitable for extracting the land water interface because it exhibits a strong contrast between land and water features due to the high degree of absorption of the mid-infrared wavelength by water (Manavalan et al, 1993;Kelly et al, 1998;Frazier and Page, 2000;Lee et al, 2001;Alesheikh et al, 2007).…”
Section: Density Slicingmentioning
confidence: 99%
“…To retrieve the SS concentration from GOCI TOA (top-of-atmosphere) data, atmospheric correction was initially performed for all GOCI images. The modified MUMM approach was used (Ruddick et al, 2000;Choi et al, 2012;Lee et al, 2013), in which contributions by aerosol and water to satellite reflectance are estimated on a per-pixel basis, with the assumption of spatially constant band-7:band-8 ratios for aerosol reflectance (ε) and water reflectance (α). Each GOCI image was converted to radiance on the sea surface (L w ), and L w was converted to remote sensing reflectance (R rs ) using the extraterrestrial solar irradiance (F o ) values for each GOCI band.…”
Section: Datamentioning
confidence: 99%